Music production in the intercultural sphere: challenges and opportunities - Huyssen, Hans (Acta Academica: Critical views on society, culture and politics, 2012)
As a South African composer working in a culturally, politically and ecologically heterogeneous environment, I deliberately refer to musical ‘differences’ in many of my works. The artistic vision developed in these works finds expression in the fusion of ‘differences’ and often highly disparate materials into unified forms of expression. In this article I respond to Kofi Agawu’s contestation of ‘difference’ from a complexity perspective indebted to Edgar Morin’s reflections on diverse systems and Paul Cilliers’s interpretation of non-foundational complexity. I use informed performance practice to respond to the overarching topic of this volume – translation – and offer a discussion of my composition The Songs of Madosini (2002) as an instance of cultural translation.